2007
DOI: 10.1016/j.neuro.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological function in children with blood lead levels <10μg/dL

Abstract: Clear adverse effects of blood lead levels >or=10 microg/dL have been documented in children. Given that the majority of US children have levels below 10 microg/dL, clarification of adverse effects below this cutoff value is needed. Our study evaluated the associations between blood lead levels <10 microg/dL and a broad spectrum of children's cognitive abilities. Data were analyzed from 534 children aged 6-10, enrolled in the New England Children's Amalgam Trial (NECAT) from the urban area of Boston, Massachus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
152
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(170 citation statements)
references
References 29 publications
15
152
1
1
Order By: Relevance
“…Lead toxicity has detrimental effects to the nervous system and the brain, thus impairing the memory abilities of a person. Higher blood lead levels were associated not just with lower scores on tests of neuropsychological domains, but also with lower scores on tests of academic achievement (Surkan et al, 2007) Previous study reported the same result with this study which mean cognitive score (102.55) of the children from the industrial area was significantly higher than that of the urban children (p<0.001). The McCarthy Scales of Children Abilities (MSCA) test showed that the mean General Cognitive Score or the IQ of the children in the industrial estate (102.55±12.41) was significantly higher than the children in the urban area (95.09 ± 13.98) (Zailina et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Lead toxicity has detrimental effects to the nervous system and the brain, thus impairing the memory abilities of a person. Higher blood lead levels were associated not just with lower scores on tests of neuropsychological domains, but also with lower scores on tests of academic achievement (Surkan et al, 2007) Previous study reported the same result with this study which mean cognitive score (102.55) of the children from the industrial area was significantly higher than that of the urban children (p<0.001). The McCarthy Scales of Children Abilities (MSCA) test showed that the mean General Cognitive Score or the IQ of the children in the industrial estate (102.55±12.41) was significantly higher than the children in the urban area (95.09 ± 13.98) (Zailina et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…One of the serious outcomes of lead exposure is a decline in cognitive functioning (memory, attention, language, concept formation, problem solving, executive and visuospatial functions) which also has an impact on school performance (Surkan et al, 2007). Lead toxicity has detrimental effects to the nervous system and the brain, thus impairing the memory abilities of a person.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the choice of threshold is relatively arbitrary because blood lead level thresholds indicating neurotoxic risk during childhood have not yet been established. Thus far, findings have led investigators to suggest that blood lead levels as low as 2.0 μg/dL may indicate significant neurotoxic risk [2]; findings may suggest that increments of 0.5 μg/dL distinguish whether and how neurobehavioral function is altered [16][17][18][19]. Given the complexity of child brain development, it would not be surprising to find that different brain pathways, and thus different neurobehavioral functions, are associated with different (low) level thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…Lead (Pb) exposure has been ofmajor public concern due to its well-established adverse neuro-behavioral effects on children [1,2].After phasingoutof Pb from gasoline and paint, child blood Pblevelshave significantly declinedworldwide [3,4].However, in Pb-contaminated sites such as mining andsmelting areas, childhood Pbpoisoning is still of concern [5,6].Lead exposure to children near Pb-contaminated areas include incidental ingestion of soils via hand-to-mouth behaviors and inhalation of resuspended soil particles [7,8]. Themean soil ingestion rate for children ranges from 1.2 to 23mg soil per day [9].…”
Section: Introductionmentioning
confidence: 99%